Good Governance: The UNP Experience - Agustin, Antonio (Social Sciences and Development Review, 2016)
Maximization and wise use of financial resources in the University of Northern Philippines is undeniably critical to its operation. Greater and better quality of outputs are derived and the university become doubly productive. The objective of this paper is to describe the development and management of infrastructure projects in UNP with emphasis on the allocation and utilization of financial resources for such projects. The study covers all infrastructure projects implemented under the administration of its president, Dr. Gilbert R. Arce in his attempt to make the university “A Global University Anchored on Excellence.” As part of the 10 Governance Initiatives of Pres. Gilbert R. Arce to attain Quality and Excellence, prioritization expenditures shall govern spending and judicious utilization of resources shall be ensured. Consultation and empowerment shall guide the process of policy formulation. As such, leadership with good governance shall be guided by the principle of transparency, responsiveness, consensus orientation, equity, economy, effectiveness and efficiency, accountability and strategic vision. The University of Northern Philippines’ good governance is epitomized by predictable, open, and enlightened policy making institution imbued with a professional ethos acting in furtherance of the public good, the rule of law, and transparent process. This paper utilized the qualitative method of research and made use of the Program Project Management Plan, Annual Procurement Plan, Bids and Awards Committee documents and information, and data provided by the Directors of the University Planning Office, Finance Services Division, and Infrastructure Planning and Development Office of the University.
Keywords: Governance Initiatives; Transparency Process; Strategic Vision; Consensus Orientation; Economy; Efficiency and Effectiveness